2014
DOI: 10.1097/htr.0000000000000020
|View full text |Cite
|
Sign up to set email alerts
|

US Population Estimates of Health and Social Outcomes 5 Years After Rehabilitation for Traumatic Brain Injury

Abstract: Significant mortality and morbidity were evident at 5 years postinjury. The deterioration in global outcomes observed regardless of age suggests that multiple influences contribute to poorer outcomes. Public health interventions intended to reduce post-acute inpatient rehabilitation mortality and morbidity rates will need to be multifaceted and age-specific.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
134
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 16 publications
10
134
1
1
Order By: Relevance
“…Seel and colleagues [12] demonstrated that 27% of individuals with TBI met diagnostic criteria for MDD based on symptoms endorsed on the Neurobehavioural Functioning Inventory [7]. Five years after TBI, depression may be most prevalent for individuals aged 40 to 49 years relative to younger or older people [13].…”
Section: Structured Clinicalmentioning
confidence: 99%
“…Seel and colleagues [12] demonstrated that 27% of individuals with TBI met diagnostic criteria for MDD based on symptoms endorsed on the Neurobehavioural Functioning Inventory [7]. Five years after TBI, depression may be most prevalent for individuals aged 40 to 49 years relative to younger or older people [13].…”
Section: Structured Clinicalmentioning
confidence: 99%
“…Studies show that patients leaving hospitals against medical advice after TBI had higher rates of readmission 12,13 . Corrigan and colleagues (2014) 14 pointed out that age-specific interventions are needed to reduce post-acute inpatient rehabilitation mortality in TBI. For patients with stroke, Slocum and colleagues (2006) 15 found that age and functional status were better predictors of hospital readmission across nine years compared to medical comorbidities; however, such age-specific association remains unclear for the TBI population.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 There also is mounting clinical and experimental evidence that TBI increases problem alcohol intake. [9][10][11][12] Problem drinking also greatly increases the chances for additional TBI later in life, which can produce much greater impairments in previously injured patients. 4 Children who suffer TBI are less likely to complete their education, find employment, and marry, and are more likely to suffer from poor health, neurological symptoms, and psychiatric ailments, which interact with, or are exacerbated by, alcohol misuse.…”
mentioning
confidence: 99%